2015
DOI: 10.1002/mnfr.201500382
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to aflatoxin and micronutrient status among young children from Guinea

Abstract: Scope Aflatoxin exposure coincides with micronutrient deficiencies in developing countries. Animal feeding studies have postulated that aflatoxin exposure may be exacerbating micronutrient deficiencies. Evidence available in human subjects is limited and inconsistent. The aim of the study was to investigate the relationship between aflatoxin exposure and micronutrient status among young Guinean children. Method and results A total of 305 children (28.8 ± 8.4 months) were recruited at groundnut harvest (rainy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Another shortcoming of ELISA is that it relies on specific antibodies for each mycotoxin; therefore, it is not appropriate for multi-mycotoxin determination. In fact, ELISA was applied in just 15% of all studies reviewed [73][74][75][76][77][78][79].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
See 3 more Smart Citations
“…Another shortcoming of ELISA is that it relies on specific antibodies for each mycotoxin; therefore, it is not appropriate for multi-mycotoxin determination. In fact, ELISA was applied in just 15% of all studies reviewed [73][74][75][76][77][78][79].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
“…To release AFB1-lysine (AFB1-lys) adduct from albumin, proteins in serum samples are digested with Pronase ® for a few hours at 37 • C. AFB1-lys is then extracted and purified with SPE by means of a mixed-mode anion exchange reversed-phase matrix. Next, the analytes are eluted, mainly through the use of methanol (MeOH) with formic acid, then concentrated and reconstituted in the mobile phase before analysis with LC-MS/MS [49,65,81,83,87,[112][113][114][115], LC-FLD [81,[88][89][90][91][92] or ELISA [73][74][75][76][77][78][79]117]. McCoy et al (2008) [70] and Scholl et al (2006) [123] reported good correlations of the concentration levels obtained from ELISA, LC-FLD and LC-MS.…”
Section: Mycotoxin Biomarkers In Human Blood Plasma and Serummentioning
confidence: 99%
See 2 more Smart Citations
“…Some findings of significant decrease in vitamin A associated with AF-ALB suggest that aflatoxin exposure compromises the micronutrient status of people who are immunocompromised, including people living with HIV (Obuseh et al, 2011). The interaction between aflatoxin and micronutrient deficiencies warrants more investigation (Watson et al, 2016;Watson et al, 2017).…”
Section: Research/data Gapsmentioning
confidence: 99%